Structural capital value addition to timber and related industries value chain - Fernandez-Jardón, Carlos-Maria; Silva, Amândio F. C. da (Revista de Administração da UFSM, 2020)
Purpose – Structural capital is a component of intellectual capital. Its measurement is essential to obtain the real value of intellectual capital and its influence on profitability. This article aims at understanding the impact of structural capital on timber and related industries value chain of Galicia (Spain). Design/methodology/approach – The wood sector chain was divided into three major sectors: extraction, conversion and finished products. Using a panel data model, we measured the value addition created by structural capital for the period of 2002-2018. Findings – Structural capital brings value addition to extraction and finished products sectors of the value chain. The sector and the territory limit value generation and efficiency of structural capital. Research limitations/implications – We took an extensive data set ranging from 2002 to 2018 of a relatively small region (Galicia). The findings could change if the area is expanded and/or other regions covered. Practical implications – For business managers and consultants, this study suggests the need for benchmarking and cooperation practices between companies to increase efficiency. Entrepreneurs must concentrate more on intellectual capital in order to better performance. Social implications – Local governments and social entities should acknowledge the importance of intellectual capital while implementing regulations and specific actions to improve SMEs profitability. Originality/value – This paper measures the impact of structural capital on the timber value chain. SC is taken as an independent variable, unlike previous measurement models, where it was a remainder value after deducting HC from IC.